Sensory Abnormalities in Focal Hand Dystonia and Non-Invasive Brain Stimulation - Quartarone, Angelo; Rizzo, Vincenzo; Terranova, Carmen; Milardi, Demetrio; Bruschetta, Daniele; Ghilardi, Maria Felice; Girlanda, Paolo (Frontiers in Human Neuroscience, 2014)
It has been proposed that synchronous and convergent afferent input arising from repetitive motor tasks may play an important role in driving the maladaptive cortical plasticity seen in focal hand dystonia (FHD). This hypothesis receives support from several sources. First, it has been reported that in subjects with FHD, paired associative stimulation produces an abnormal increase in corticospinal excitability, which was not confined to stimulated muscles. These findings provide support for the role of excessive plasticity in FHD. Secondly, the genetic contribution to the dystonias is increasingly recognized indicating that repetitive, stereotyped afferent inputs may lead to late-onset dystonia, such as FHD, more rapidly in genetically susceptible individuals. It can be postulated, according to the two factor hypothesis that dystonia is triggered and maintained by the concurrence of environmental factors such as repetitive training and subtle abnormal mechanisms of plasticity within somatosensory loop. In the present review we examine the contribution of sensory-motor integration in the pathophysiology of primary dystonia. In addition will discuss the role of non invasive brain stimulation as therapeutic approach in focal hand dystonia.